Racionalidad y Justicia Ambiental: La Elusiva Injusticia de la Vida - Leff, Enrique (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2021)
Law is not justice, says the Manifesto for Life. The justice system established in modernity (the legality of a positive law) does not manage to contain the will to dominate exercised by the ontological regime of modernity over the degradation of life and to adjust human behavior within the conditions of life. Environmental justice transcends the order of the economy (even of the ecological economy) as a mechanism of the social distribution of human justice of environmental goods and services of nature, to institute another idea of ​​fairness under the principles of human dignity and in the immanence of life. Environmental justice seeks to establish a criterion of fairness for the construction of other possible worlds based on the principles that sustain the disjunctive category of environmental rationality: an ontology of the diversity of life, a politics of difference, and ethics of otherness.